Pendampingan Penanganan Siswa Problematik Melalui Pendekatan BTQ Di MTs. Miftahul Ulum Tanjungarum - Natasya Hayomi Salsabila; Miftakhul Khoiriyah; Siti Julaikha; Sofi Fauziyah; Miftara Ainul Mufid (CV. Devi Tara Innovations, 2025)
This study aims to explore the implementation of mentoring in addressing problematic students at MTs Miftahul Ulum Tanjungarum through the Qur'anic reading and writing approach. This approach is expected to help students facing behavioral, social, and academic issues find solutions through the moral values contained in the Qur'an. The research employs a descriptive qualitative method with data collection through interviews, observations, and documentation. The findings indicate that the mentoring program through Qur'anic reading and writing has a positive impact on improving students' behavior, social skills, and academic performance. The mentoring process involves teaching values such as honesty, discipline, and patience, which can be applied in everyday life. This study is expected to contribute to the development of student mentoring strategies in Islamic education-based schools